Situating the self : gender, community, and postmodernism in contemporary ethics - Benhabib, Seyla (Polity Press, 1992)
Focusing on contemporary debates in moral and political theory, Situating the Self argues that a non--relative ethics, binding on us in virtue of out humanity, is still a philosophically viable project. This intersting new book should be read by all those concerned with the problems of critical theory, the analysis of modernity, and contemporary ethics, as well as students and professionals in philosophy, sociology and political science.